The dynamic effects of subway network expansion on housing rental prices using a repeat sales model - Lee, Chang Moo; Ryu, Kang Min; Choi, Keechoo; Kim, Jin Yoo (International Journal of Urban Sciences, 2018)
This study investigates the effects of subway network expansion on housing rent in existing station areas in Seoul, where subway lines had been added continuously during the sample period from 2000 to 2012. Due to network expansion, some existing stations have been enjoying improvements in network accessibility while others have not. The gap in accessibility improvement between the two groups is causing differentiated levels of capitalization in nearby housing rent. In this study, a modified repeat sales model was developed to detect the inter-temporal changes of rent gradient from the affected subway stations. Based on the model, the time trends of the rent gradients for the two groups were compared. The estimation results show that the marginal value of a proximity of 100 m to a subway station was increased by about 0.6% during the 12 year period. Furthermore, it was found that the marginal value was increased by 0.8% for the more improved group of network accessibility, while only about 0.2% for the less improved. These findings confirm that network expansion of subway lines benefits subway users in existing subway areas as well as those in new station areas, and that those benefits are capitalized into housing rent.
Keywords: accessibility; housing rent; Network expansion; repeat sales model; subway; value effect